مدى توافق النظام المحاسبي المالي "SCF" مع المعايير المحاسبية الدولية "IAS/ IFRS": دراسة تحليلية تقييمية - سعيداني، محمد السعيد; بوبكر، رزيقات (المركز الجامعي أحمد بن يحي الونشريسي تيسمسيلت - معهد العلوم الاقتصادية والتجارية وعلوم التسيير, 2018)
The Algerian financial accounting system has been modified and amended in order to improve the efficiency of accounting systems in economic institutions to serve interested parties and beneficiaries of financial reports. Algeria has adopted international accounting standards through Law No. 07/11 of 25 November 2007, which includes the financial accounting system. Through the research study, I found that the financial accounting system is largely in line with international accounting standards. However, it can be observed that IAS / IFRS is a fast-updating standard according to economic conditions and conditions, similar to the accounting system. It is therefore possible to say that after seven years of starting the application of the financial accounting system it became necessary to study the reality of this system and the problems facing its application.
عرف النظام المحاسبي المالي الجزائري تغييرا وتعديلا من أجل رفع كفاءة الأنظمة المحاسبية في المؤسسات الاقتصادية لخدمة الأطراف المهتمة والمستفيدة من التقارير المالية وعليه تبنت الجزائر المعايير المحاسبية الدولية من خلال القانون رقم 07/11 المؤرخ في 25 نوفمبر 2007 المتضمن النظام المحاسبي المالي. من خلال الدراسة البحثية وجدنا أنا النظام المحاسبي المالي يتوافق إلى حد كبير مع المعايير المحاسبية الدولية، غير أن ما يمكن ملاحظته أن المعايير المحاسبية الدولية(IAS/IFRS) هي معايير سريعة التحديث وفق المستجدات والظروف الاقتصادية على غرار النظام المحاسبي المالي. وعليه يمكن القول إنه بعد مرور سبعة سنوات من البدء في تطبيق النظام المحاسبي المالي أصبح من الضروري دراسة واقع هذا النظام والمشاكل التي تواجه تطبيقه.
Keywords: المعايير المحاسبية -- التوافق المحاسبى -- التقارير المالية